Apparatus, system and method for making carbanogel buckypaper from carbon dioxide and products thereof

JP2024522417A5Inactive Publication Date: 2025-04-15DIRECT AIR CAPTURE LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023531607
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-20
Filing Date
2022-05-20
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Embodiments of the present disclosure relate to a process for making carbanogel buckypaper products. Such carbanogel buckypaper products may be endowed with improved properties compared to other buckypaper products. In some embodiments of the present disclosure, the carbanogel may be produced by an electrolysis process that may convert carbon-containing gases into carbon nanomaterials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 191,122, filed May 20, 2021, the entire contents of which are incorporated by reference herein.

[0002]

[0002] The present disclosure relates to the manufacture of products using an electrolysis process. In particular, the present disclosure relates to a method of making a carbanogel product from carbon dioxide split using an electrolysis process. [Background technology]

[0003]

[0003] Buckypaper is a sheet of carbon nanomaterials (CNM). The majority of studies have reported buckypaper composed of carbon nanotubes. Additionally, buckypaper can be composed of graphene, graphene oxide, and carbon nanotubes and has been studied.

[0004]

[0004] Buckypaper exhibits a variety of improved physical and chemical properties, including, but not limited to, high tensile strength, high electrical conductivity, high thermal conductivity, electronic shielding, magnetic shielding, charge storage for use in batteries, fuel cells and capacitors, catalytic activity, reduced friction and targeted therapeutic activity. Many of these properties are derived from the planar sp2 bonded carbon of graphene in different geometric configurations, including single or coaxial graphene cylinders, multi-walled (carbon nanotubes, CNTs), carbon nanofibers, single or multi-walled (nanoplatelet) graphene, hollow or coaxial (nano-onion) buckyball spheres and three-dimensional geometries, such as graphene nanoscaffolds.

[0005]

[0005] The acceptance and widespread use of buckypaper has been hindered by the expense of manufacturing CNM components and the associated high carbon footprint. The manufacturing process involves a chemical vapor deposition (CVD) process that is traditionally used in the commercial manufacture of CNMs. Currently, CNMs, such as CNTs, graphene, and carbon nano-onions, cost between $100,000 USD and $10,000,000 USD per ton. In comparison, steel costs between $400 and $700 USD per ton.

[0006]

[0006] In a typical buckypaper formation process, the CNMs are first added to a liquid, then ultrasonically decomposed to provide a uniform dispersion, and the liquid is filtered and / or dried to leave the buckypaper formed as a solid sheet of dispersed CNMs.

[0007]

[0007] Therefore, new methods of commercial production of buckypaper that address the high costs and associated high carbon footprint are desirable. Summary of the Invention

[0008]

[0008] An embodiment of the present disclosure relates to a process for fabricating or otherwise producing sheets of carbon nanomaterials (CNM), referred to herein as buckypaper products, from carbanogel, which may have lower CO2 levels. The process includes forming CNM with carbanogel product by a melt electrolysis process for splitting carbon dioxide (CO2), recovering the carbanogel product by pressing, sieving, peeling and / or crushing the carbanogel product or a combination thereof, transferring the crushed carbanogel product to a mold with or without filtration and with or without chemical, thermal, mechanical or electrochemical treatment, and compressing the carbanogel product in the mold to form the buckypaper product.

[0009] Some embodiments of the present disclosure relate to carbanogel buckypapers (CBs) comprising carbon nanomaterials (CNMs) and an electrolyte.

[0010] Some embodiments of the present disclosure relate to a system for making carbanogel buckypaper, the system including an apparatus for performing an electrolysis process of splitting carbon dioxide (CO2) in a molten electrolyte to produce carbanogel, the carbanogel including carbon nanomaterials (CNM) and an electrolyte, a mold, and a compression unit. [Brief description of the drawings]

[0011]

[0011] These and other features of the present disclosure will become more apparent from the following detailed description, in which reference is made to the accompanying drawings.

[0012] [Figure 1] 1 is a schematic diagram of an apparatus for making a carbanogel product for use in embodiments of the present disclosure. [Diagram 2]

[0013] FIG. 1 is a schematic diagram of a system according to an embodiment of the present disclosure for making a carbanogel buckypaper product. [Diagram 3]

[0014] 1 is a schematic diagram illustrating steps of a method according to an embodiment of the present disclosure. [Figure 4]

[0015] 5 is a schematic diagram illustrating further method steps according to an embodiment of the present disclosure. [Diagram 5]

[0016] 1 is a photograph of a carbanogel buckypaper made according to an embodiment of the present disclosure. [Figure 6]

[0017] 1 is a photograph of additional carbanogel buckypaper made according to an embodiment of the present disclosure. [Figure 7]

[0018] 3 shows photographs of scanning electron microscope images of carbanogels made according to embodiments of the present disclosure, the top image showing an image at 730x magnification and the bottom image showing an image at 8600x magnification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013]

[0019] Since 2009, the energy-efficient conversion of CO2 to carbon and oxidation by molten carbonate electrolysis has been known. Subsequently, the chemical conversion of CO2 to various graphitic carbon nanomaterials (CNMs) has been demonstrated. These graphitic CNMs are valuable due to their long-term stability and the useful properties that these materials possess, such as ultra-high strength, high electrical and thermal conductivity, high battery capacity, electromagnetic radiation shielding, effective drug delivery and various medical properties, as well as useful catalytic properties. CO2→C ナノ物質 +O2 (formula 1)

[0014]

[0020] Equation 1 shows the melt electrolysis process, where carbon nanomaterials grow and remain on the cathode as a mixture of entangled CNMs mixed with electrolyte. This mixture is called a carbanogel, and at least 95% of the electrolyte can be extruded from the carbanogel by hot press filtration.

[0015]

[0021] Graphene sp , which may occur within the CNM component 2The inclusion of bound carbon components and single or multi-layer graphene may provide improved properties to the CNMs in the carbanogel, such as, but not limited to, enhanced strength and conductivity of these CNMs. Additionally, the relative amounts of certain morphologies of CNMs may impart additional properties to the carbanogel and products made therefrom. Examples of such morphologies include, but are not limited to, spherical nanocarbons, solid and hollow nano-onions, cylindrical allotropes of nanocarbons, planar allotropes, helical allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface-modified or metal-coated CNMs, amorphous nanocarbons without geometrical features or characteristics, or any combination thereof. Examples of such additional properties include, but are not limited to, reduced friction, elasticity, thermal conductivity, flame retardancy, chirality, improved surface area, or any combination thereof, of the CNMs in the carbanogel. These properties are useful for certain applications including, but not limited to, lubrication, flexible materials, chiral light absorption, chiral light emission, chiral catalysis, improved electrochemical charge storage, improved catalytic activity, fire resistance, or enhanced EMF shielding capabilities. The CNMs in the carbanogel may also include additional features including doping, magnetism, unusual shapes, and miniaturized or enlarged sizes. Without being bound by any theory, the CNTs may be single-walled CNTs, multi-walled CNTs, doped CNTs, such as boron, sulfur, phosphorus or nitrogen doped CNTs, magnetic CNTs, bamboo-shaped CNTs, pearl-shaped CNTs, isotopically specific CNTs, such as 12 C and 13 The CNTs may include CCNTs, surface modified or metallized CNTs, helical CNTs including single or double braided CNTs, spiral helical CNTs, thin, thick or solid wall CNTs, small and large diameter CNTs, short or woolly (long) CNTs, or any combination thereof.

[0016]

[0022] According to an embodiment of the present disclosure, a carbon-containing gas may undergo an electrolysis process, also referred to herein as an electrosynthesis process, to generate a carbanogel comprising a carbon nanomaterial (CNM) product from the carbon in the gas. The term "carbanogel" is used herein to refer to a mixture of CNMs and electrolyte that is a product of the electrolysis process and is localized at the cathode during or after the electrolysis process. The terms "carbon nanomaterial product" and "CNM product" are used herein to refer to a collection of nanocarbon, which may also be referred to as nanoscale carbon, in one or more forms. The term "nanocarbon" is used herein to refer to carbon arranged at the nanoscale in a specific structure, e.g., a graphitic nanocarbon structure. In particular, carbon from a carbon-containing gas may be split into carbon and oxygen using a molten electrolyte medium and various electrolysis process configurations. The electrolysis process may cause mass transfer of carbon from the gas phase to the molten electrolyte medium, the solid CNM product, or both. The CNM product may be substantially pure, pure, or impure carbon nanomaterial (CNM) including carbon nanotubes (CNTs). The CNM product may include one or more forms of CNM structures as described hereinabove, or any combination thereof. Optionally, one or more parameters of the electrolysis process may be adjusted to vary the relative amounts of a given form in the CNM product.

[0017]

[0023] As shown in FIG. 1, the electrolysis process may take place in an apparatus 10 including a case 12, which may be referred to as an electrolysis chamber or electrolysis cell, for housing a cathode 18, and an anode 16 may form at least a portion of the inner surface of the wall of the case 12. Together, the two electrodes define an electrolysis space between them. Optionally, the anode 16 may be separate from the wall of the case 12, as will be appreciated by those skilled in the art. The case 12 is configured to house an electrolyte medium 21. The electrolysis space B, including the top surface 21A of the electrolyte, may be in fluid communication with a carbon-containing gas source (shown as D in FIG. 1). In some embodiments of the present disclosure, the case 12 may be contained within an insulated housing 20 made of a thermal insulating material. The insulated housing 20 may also include a top 22 or sides or bottom (not shown) made of a thermal insulating material or not, and the thermal insulating material may be derived from a CO2-permeable insulating material, such as a high-temperature woven ceramic or a substantially CO2-impermeable insulating material. Examples of permeable insulation materials include, but are not limited to, Morgan Cerablanket®, made from oxides of alumina and silica and may contain zirconia, and Morgan Superwool®, made from alkaline earth silicates, both of which are suitable for temperatures above 1,200° C. Examples of substantially CO2 impermeable insulation materials include the wide range of commercially available firebricks or cast-in-place refractory cements and mortars, examples of which include, but are not limited to, BNZ Materials firebricks and refractory cements and mortars suitable for temperatures above 1,090° C., such as PA20 and 23, and BNZ2000, 2300, 23A, 2600, 26-60, 2800, 3000 and 3200.

[0018]

[0024] The carbon-containing gas source may be various industrial plants including, but not limited to, cement manufacturing plants, iron refining plants, steel manufacturing plants, plants that make or use one or more of ammonia, ethanol, magnesium, hydrogen, polymers, plastics, glass, wastewater treatment plants, food processing plants. The carbon-containing gas source may also be a chemical reactor, including internal combustion engines and the combustion of carbonaceous materials for heating or cooking. Exhaust gases from power plants, steam generating equipment, or pyrolysis reactors may also be carbon-containing gas sources. Carbon-containing gases emitted from these sources or in the manufacture of any high carbon footprint material may also contribute to or constitute the carbon source for making the CNM product. Additionally, gas products and carbon products of the combustion or conversion of fossil fuels for heating, transportation, such as polymers and plastics, may also contribute to or constitute the carbon source for making the CNM product.

[0019]

[0025] In some embodiments of the present disclosure, the anode 16 may be formed as a planar structure, a wire structure, a screen, a porous structure, a conductive plate, a flat or folded shim, a coiled structure, or the anode may form at least a portion of the inner wall of the case 12. The anode 16 may be formed of a variety of conductive materials such that the anode 16 may or may not be oxygen evolving. Such anode forming materials include, but are not limited to, any conductive material that has or establishes a stable layer, Ni, Ni alloys, galvanized (zinc coated) steel, titanium, graphite, iron, and a wide variety of metals that establish a highly stable oxide outer layer that promotes oxygen production during the electrolysis reaction carried out by embodiments of the present disclosure. Further examples of suitable materials for forming the anode 16 include nickel alloy 36 (nickel without chromium but with iron), stainless steels such as SS304 or SS316, Nichromes (nickel-chromium based alloys), and Inconel alloys such as Inconel 600, 625 and 718, alloy C-264 or Nichromes such as Chromel A, B or, as co-nucleation of the alloying components is known to produce high quality CNTs. Binary and ternary transition metal nucleating agents including, but not limited to, Ni, Cr, Sn, In, Fe and Mo may also be useful and may affect the growth of the CNM product as well.

[0020]

[0026] In some embodiments of the present disclosure, a transition metal may be added to the anode 16, which may be dissolved from the anode 16 to migrate through the electrolyte medium 21 to the cathode 18. The added transition metal may function as a nucleating agent, which may be selected from nickel, iron, cobalt, copper, titanium, chromium, manganese, zirconium, molybdenum, silver, cadmium, tin, ruthenium, zinc, antimony, vanadium tungsten, indium, gallium, or non-transition metals such as germanium or silicon or mixtures thereof, including but not limited to brass, monel, and nickel alloys. The transition metal may also be introduced directly as a transition metal salt dissolved in the electrolyte medium 21 to migrate onto the cathode 18. It is also possible to add the transition metal nucleating agent directly onto the cathode 18.

[0021]

[0027] In some embodiments of the present disclosure, the cathode 18 may be formed as a planar structure, a wire structure, a screen, a porous structure, a conductive plate, a flat or folded shim, a sheet, a coiled structure, or the cathode may form at least a portion of the inner wall of the case 12. The cathode 18 may be formed of a variety of conductive materials reflecting the need for nucleation points and variations in the CNM products that form on the cathode 18. Such cathode forming materials include, but are not limited to, any conductive material, galvanized (zinc coated) steel, titanium, graphite, iron, alloys including copper and zinc, Monel (Ni400, Ni / Cu alloy), Inconel, stainless steel, iron, nichrome, pure Cu, and brass alloys may also be suitable materials for making the cathode 18.

[0022]

[0028] The anode 16 and the cathode 18 may be aligned substantially parallel to each other within the case 12, such as a stainless steel case or a case made of substantially pure or pure alumina. The case 12 may be made of any material suitable for containing the molten electrolyte medium 21 and maintaining the temperature achieved by the device 10A. The electrodes may be oriented in any orientation, including but not limited to substantially horizontal or substantially vertical, but are spaced apart from each other to define an electrolysis space B therebetween. In some embodiments of the present disclosure, the electrolysis space B is about 0.1 cm to about 10 cm. In some embodiments of the present disclosure, the electrolysis space B is about 1 cm. As will be appreciated by those skilled in the art, the dimensions of the electrolysis space B depend on the scale of the device 10, such as the size of each electrode, the plenum defined within the case, the amount of current applied, and combinations thereof.

[0023]

[0029] The anode 16 and the cathode 18 are operably connected to a current source (not shown), which may be any source of AC or DC, either constant or not, that provides a current density of about 0.001 A / cm2 to 10 A / cm2. In some embodiments of the present disclosure, the current density provided between the electrodes is at least 0.02 A / cm2.2 , 0.05A / cm 2 , 0.1A / cm 2 , 0.2A / cm 2 , 0.3A / cm 2 , 0.4A / cm 2 , 0.5A / cm 2 , 0.6A / cm 2 , 0.7A / cm 2 , 0.8A / cm 2 , 0.9A / cm 2 , 1.0A / cm 2 The power for the current source can be any source or combination of sources including mains, solar power, and the like.

[0024]

[0030] The heat source (not shown) can be any heat source that raises the temperature within the case 12 to a temperature that transitions the electrolyte medium 21 into a molten phase. For example, the heat source can achieve a temperature within the case 12 of about 500°C to about 850°C or greater. In some embodiments of the present disclosure, the heating achieves a temperature of about 700°C to about 800°C, about 720°C to about 790°C, or about 750°C to about 780°C. In some embodiments of the present disclosure, the heating achieves a temperature of 749-750°C, 751-752°C, 753-754°C, 755-756°C, 757-758°C, 759-760°C, 761-762°C, 763-764°C, 765-766°C, 767-768°C, 769-770°C, 771-772°C, 773-774°C, 775-776°C, 777-778°C, or 779-780°C. In some embodiments of the present disclosure, the temperature within the case 12 can be increased to about 800°C or higher. In some embodiments of the present disclosure, the heat source is provided or supplemented by the exothermic reaction of CO2 absorption and conversion to carbonate (mass transfer from gas phase to solid phase CNM product) or by the overpotential of the applied electrolysis current.

[0025]

[0031] In some embodiments of the present disclosure, the electrolyte medium may include a carbonate that can be heated by a heat source until it transitions to a molten phase. For example, the carbonate may be lithium carbonate or a lithiated carbonate. Molten carbonates such as lithium carbonate (Li2CO3) with a melting point of 723°C or lower melting point carbonates such as LiBaCaCO3 with a melting point of 620°C, if they include oxides, include spontaneous oxide formation that occurs upon melting or is the result of electrolysis, or when mixed with highly soluble oxides such as Li2O, Na2O, and BaO, sustain rapid absorption of CO2 from the space above the molten electrolyte medium. Suitable carbonates may include alkali carbonates and alkaline earth carbonates. Alkaline carbonates may include lithium, sodium, potassium, rubidium, cesium, or francium carbonates or mixtures thereof. Alkaline earth carbonates may include beryllium, magnesium, calcium, strontium, barium, or radium carbonates or mixtures thereof. In some embodiments of the present disclosure, the electrolyte may be a mixed composition, such as a mixture of one or more of alkali and alkaline earth carbonates and oxides, borates, sulfates, nitrates, chlorides, chlorates, or phosphates.

[0026]

[0032] According to an embodiment of the present disclosure, the carbanogel is formed by molten carbonate electrolysis splitting of CO2. The carbanogel comprises a mixture of CNM network and electrolyte that remains after the electrolysis process is stopped. Interestingly, not only can the carbanogel maintain the CNM network after fracturing, but the fractured pieces can be reassembled to form buckypaper. Some, most, substantially all or all of the electrolyte can be removed from the buckypaper by pressing, reacting or washing away the electrolyte. Pressing the fractured pieces with or without electrolyte can result in a continuous layer that can be called "carbanogel buckypaper" (CB). After removal of some or all of the electrolyte, the carbanogel consists of CNMs composed of high purity carbon. After removal of some or all of the electrolyte, the CB defines an interior void. For example, the CB can define void spaces in the CB, on the CNM surface in the CB, within the CNM (inside the CNM), or a combination thereof. For purposes of this disclosure, the term "void" refers to a two- or three-dimensional space in the CB that is substantially free of electrolyte or other materials.

[0027]

[0033] In some embodiments of the present disclosure, the voids defined in the CB can be partially, substantially completely or completely filled with a void-filling agent, such as a material based on the application. Examples of suitable void-filling agents include, but are not limited to, reinforcing agents, catalysts, dopants, drugs or electromagnetic field (EMF) shielding agents. Reinforcing agents can include, but are not limited to, epoxy resins, resins and other polymers, cementitious materials and metals. Catalysts can include, but are not limited to, materials for promoting chemical or electrochemical reactions. Dopants can include, but are not limited to, materials that substantially affect the physical and chemical properties of the CB in small amounts within the voids. The CNM components in the CB can be mechanically, electrically or magnetically aligned during CB formation to further enhance CB properties, including, but not limited to, strength, electrical and thermal properties. Electrical and / or magnetic alignment is achieved by applying an orienting electric and / or magnetic field during the CB preparation stage. Magnetic CNMs are prepared by incorporating magnetic materials, such as metals or metal carbides, during the electrolysis process when generating CNMs. CB sheets may be used, for example, in backings, fire retardants, or shielding, alone or in combination with other materials, such as, but not limited to, laminates, to impart improved properties to those other materials.

[0028]

[0034] It is known that the high production costs of CNM are primarily due to high reactant and energy costs. Without being limited by any particular theory, when produced from CO2 using a melt electrolysis process according to embodiments of the present disclosure, these production costs can be reduced by two orders of magnitude.

[0029]

[0035] Some embodiments of the present disclosure relate to a system 200 for making a CB product 222. As shown in the non-limiting example of Figure 2, the system 200 includes an apparatus 210 for performing an electrolysis process of splitting carbon dioxide (CO2) in a molten electrolyte to produce a carbanogel, a mold 212, and a compression unit 214. The system 200 can be used to implement the methods of the present disclosure as described herein below.

[0030]

[0036] In some embodiments of the present disclosure, the apparatus 210 can be the same as or similar to the apparatus 10 described herein above. The apparatus 210 is configured to perform an electrolysis process that splits a carbon-containing gas in a molten electrolyte. The product of that splitting is a CNM product, or carbanogel, which may also be referred to as a carbanogel product, with bulk or residual electrolyte therein.

[0031]

[0037] The mold 212 is a vessel that receives the carbanogel (represented by line X in FIG. 2), whether as a cold product or a hot product. The mold 212 can be made of a variety of materials and can be of any shape and size, so long as the mold 212 is robust enough to withstand the temperatures and pressures that may be applied to the carbanogel therein. The CB product 222 is received from the mold 212, and optionally, the system 200 can further include an insulating unit 224 to protect the CB product 222 from an oxidizing environment. The insulating unit 224 can include a suitable sized fluid seal to receive the CB product 222, remove any oxidizing agents, such as oxygen-containing gas, from the vessel, for example by a vacuum pump, and replace the fluid in the vessel with a non-oxygen-containing gas, such as an inert gas.

[0032]

[0038] The compression unit 214 can be a variety of suitable components, mechanisms, or machines that apply a compressive force to the carbanogel in the mold 212. The magnitude of the compressive force can vary depending on the size of the carbanogel particles received by the mold 212 and how much electrolyte the carbanogel contains, as discussed further below. In some embodiments of the present disclosure, the compression mechanism 214 includes a vacuum that can pull the carbanogel (shown by line Y in FIG. 2) through a filter or into the mold 212.

[0033]

[0039] In some embodiments of the present disclosure, the system 200 may further include a processing unit 216 for crushing the cooled or hot carbanogel product prior to (or after) receipt by the mold 212. The processing unit 216 may be any suitable component, mechanism, or machine capable of withstanding the temperatures of the carbanogel, such as, but not limited to, a grinder, a mincing unit, a physical press, a pulverizing unit, a mill, or any combination thereof. The resulting particle size of the carbanogel is determined by the extent of the processing operations performed by the processing unit 216.

[0034]

[0040] In some embodiments of the present disclosure, the system 200 may further include an electrolyte reduction unit 218. The electrolyte reduction unit 218 may receive the cooled or hot carbanogel product directly from the apparatus 210 and / or it may receive the treated carbanogel product from the processing unit 216. The electrolyte reduction unit 218 reduces the electrolyte content of the carbanogel product (treated or untreated) such that the carbanogel with reduced electrolyte content may be processed (or further processed) in the processing unit 216 and then received by the mold 212. Alternatively or additionally, the carbanogel with reduced electrolyte content may be received by the mold from the electrolyte reduction unit 218.

[0035]

[0041] The electrolyte reduction unit 218 may reduce the electrolyte content of the carbanogel (treated or untreated) by mechanical, chemical, electrochemical, or any combination thereof. For example, the mechanical methods may include various suitable components, mechanisms, or machines that may reduce the electrolyte content of the carbanogel, such as a mechanical press that pushes the carbanogel through a mesh or sieve, a heater to dissolve the electrolyte in the carbanogel, a filter (room temperature or high temperature), or any combination thereof. The chemical methods for reducing the electrolyte content of the carbanogel include one or more washing stations for exposing the carbanogel to one or more chemicals that may dissolve the electrolyte. In addition to reducing the electrolyte content, one or more chemicals may also be added to dissolve impurities such as amorphous carbon or metals from the CNMs in the carbanogel. The electrochemical methods include an apparatus for performing selective electrolysis to reduce the electrolyte content and / or impurity content of the carbanogel.

[0036]

[0042] In some embodiments of the present disclosure, the system 200 may further include an alignment unit 220 for aligning at least a portion of the carbanogel (treated and / or electrolyte-reduced or not) and / or CNM components in the CB product (as shown in the non-limiting example of FIG. 2). The alignment unit 220 may be integrated into the mold 212 such that the alignment procedure performed by the alignment unit 220 occurs within the mold. Alternatively or additionally, the alignment unit 220 may be a separate physical component from the mold 212 that can receive the uncompressed carbanogel (treated and / or electrolyte-reduced or not), perform the alignment procedure, and then transfer the aligned carbanogel to the mold 212. The alignment unit 220 may use one or more of mechanical, electrical, magnetic, or any combination thereof, such that the aligned CNM components in the CB product have the required anisotropic properties. The alignment unit 220 may use a mechanical approach with various suitable components, mechanisms, or machines that can apply an orienting physical stress field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or CB product. For example, the mechanical approach may apply a shear force to the CNMs product in the carbanogel. The shear force may be applied by pulling, rotating, or pulling a body, such as a piston, through the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or CB product. Alternatively, the shear force is applied directly to increase CNM entanglement rather than CNM alignment.

[0037]

[0043] The alignment unit 220 may use an electrical approach via a variety of suitable components, mechanisms, or machines that can apply an orienting electric field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or CB product.

[0038]

[0044] The alignment unit 220 may use a magnetic approach by various suitable components, mechanisms, or machines that can apply an orienting magnetic field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or CB product.

[0039]

[0045] In some embodiments of the present disclosure, alignment unit 220 may be used to reduce rather than increase the directional alignment of CNMs, thus reducing any anisotropic properties of the CB product.

[0040]

[0046] Figure 3 shows the steps of a method 100 of making a CB product as including receiving 102 a carbanogel, placing 104 the carbanogel in a mold, compressing 108 the carbanogel, and recovering 110 the CB product. Figure 4 shows a method 100A that includes many of the steps of method 100 and the further steps of generating 101 a carbanogel by an electrolytic process as described hereinabove and treating 103 and / or reducing 105 the electrolyte content of the carbanogel.

[0041]

[0047] For the receiving step 102, the carbanogel may be generated using the electrolysis process described herein above, which may be referred to as the generating step 101. The generated carbanogel comprises the entangled product of CNMs grown at the cathode during the molten electrolysis splitting of CO2. By selectively controlling the operating parameters of the electrolysis process described above for generating step 101, the generated carbanogel may have a greater relative amount of the desired morphology of CNMs in the carbanogel. For example, the electrolysis process may be controlled to increase the relative amount of spherical nanocarbons, solid and hollow nano-onions, nanocarbons of cylindrical allotropes, planar allotropes, helical allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface modified or metal coated CNMs, amorphous nanocarbons without geometrical features or characteristics, or any combination thereof, as compared to other morphologies of nanocarbon structures within the CNMs of the carbanogel.

[0042]

[0048] The emerging carbanogel containing the CNM product may be received in a carbanogel processing step 103, which may include cooling the carbanogel, allowing it to peel or breaking off pieces of the carbanogel from the cooled cathode 18, crushing the carbanogel, or any combination thereof. Alternatively, in the processing step 103, the carbanogel containing the CNM product may be extracted from the cathode 18 while still hot and containing hot molten electrolyte, and then subjected to crushing the hot carbanogel or other steps of the method described herein. Thus, the receiving step 102 may be of a cooled and solid or hot and viscous fluid carbanogel, which may or may not undergo further processing.

[0043]

[0049] According to embodiments of the present disclosure, the processing step 103 can be performed by various manners such as crushing techniques including, but not limited to, grinding, mincing, pressing, pulverizing, milling, or combinations thereof. The resulting particle size of the carbanogel material in the carbanogel is determined by the degree of crushing. Furthermore, the resulting carbanogel particle size may constrain the minimum thickness of the CB product. Further and / or more severe crushing results in a smaller carbanogel particle size and therefore a thinner CB product compared to scenarios where the processing step 103 is performed for a shorter time and / or with less severity.

[0044]

[0050] In some embodiments of the present disclosure, the electrolyte and impurity content of the carbanogel may be reduced by the reducing step 105. Without being limited thereto, the reduced impurities may include non-graphitic carbon, such as amorphous carbon and metals, or combinations thereof. Some, most, substantially all, or all of the electrolyte and / or impurities may be removed from the carbanogel by pressing, reacting, or washing the carbanogel in a chemical, mechanical, or electrochemical manner. For example, the mechanical manner for the reducing step 105 may include applying physical pressure to the carbanogel to physically force the electrolyte out of the carbanogel through a sorting device, such as a mesh with a specific pore size. The mechanical manner may also include adjusting the temperature above the melting point of the electrolyte to facilitate electrolyte flow and separation. The melting points of the alkali and alkaline earth carbonate electrolytes range from less than 400° C. for molten ternary eutectic Li, Na, K carbonates to 891° C. for potassium carbonates. The applied pressure may range from 0 to 1000 pounds per square inch (psi), 1000 to 2000 psi, or may be 2000 psi or greater. Alternatively or additionally, reducing 105 may include chemical methods, where the carbanogel is exposed to one or more chemicals to cause a reaction that reduces the electrolyte content of the carbanogel. For example, a washing solution may be used to wash the carbanogel, where the washing solution may dissolve some of the residual or bulk electrolyte from the carbanogel particles. The washing solution may include a neutral pH liquid, such as water or a saline solution, or an acidic or alkaline solution that may facilitate dissolution of the molten electrolyte, such as formic acid or hydrochloric acid or ammonia sulfate, an oxidizing solution, such as permagnate or peroxide, or an organic solvent, or any combination thereof. In addition to reducing the electrolyte, the washing solution may be applied to dissolve impurities, such as amorphous carbon or metals, from the CNM. In some embodiments of the present disclosure, the electrolyte content of the carbanogel may be reduced by room temperature filtration and / or high temperature filtration.Further methods for reducing the electrolyte content of the carbanogel 105 include, but are not limited to, mechanical methods such as sieving and filtering, electrochemical means such as selective electrolysis, thermal means such as oxidative removal by burning of less stable amorphous carbon are applied to remove CNM impurities, or any combination thereof. Reducing the electrolyte content of the carbanogel may increase the relative proportion of CNMs in the carbanogel, which may reduce the pressure required to form the CB product. In some embodiments of the present disclosure, the step 105 of reducing the electrolyte and / or impurity content of the carbanogel may be performed once or more than once on treated or untreated carbanogels.

[0045]

[0051] During the placing step 104, the carbanogel may be placed in a mold, for example, mold 212, and then the treating step 103 and / or reducing step 105 may be performed. Alternatively, the treating step 103 and / or reducing step 105 may be performed in a vessel separate from the mold, and then the treated and / or electrolyte and / or impurity reduced carbanogel may be placed in the mold. Correspondingly, in FIG. 4, a double-headed arrow is used to represent the interchangeability of the order of the placing step 104, and the treating step 103, and the reducing step 105. The shape of the mold determines the final shape of the CB product, which is in no way limited. In some embodiments of the present disclosure, the mold may be substantially flat with a top and a bottom to make a substantially planar sheet of the CB product. In other embodiments of the present disclosure, the mold may have a desired three-dimensional (3D) shape so that the CB product has a similar 3D shape. The 3D mold may be of virtually any shape.

[0046]

[0052] Surprisingly, under compression pressure, the carbanogel particles can assemble to form a continuous sheet. Several layers of laminar, crushed carbanogel particles or one or more layers of larger carbanogel particles can be subjected to a compressing step 108 to make a CB product. For example, following compression 108, one layer of crushed carbanogel particles sized to about 25 μm will form a sheet that is about 25 μm, but less than 25 μm thick. On the other hand, four layers of 25 μm sized carbanogel particles will form a sheet that is about 100 μm, but less than 100 μm thick. Similarly, one layer of 100 μm sized carbanogel particles will form a sheet that is about 100 μm, but less than 100 μm thick.

[0047]

[0053] The steps of compressing the carbanogel 108 and applying heat 107 to the carbanogel, applying pressure 109, allowing precipitation to occur, and / or filtering, e.g., vacuum filtering 111, and aligning 113, or any combination thereof, may be repeated two or more times to ensure the formation of the desired CB product. Under various conditions, the step of applying pressure 109 may include applying a pressure of about 1 to about 1,000 psi, about 1,000 to about 2,000 psi, or pressures in excess of 2,000 psi may be applied to the carbanogel particles to form the CB product. Applying pressure 109 at or above the upper end of these ranges may be required to form sheets of the CB product that are stable at room temperature. These stable sheets of CB product may then be subjected to a further step of heating 107, optionally in a mold, to a temperature sufficient to melt the residual electrolyte within or in the carbanogel particles. The temperature required to melt the residual electrolyte depends on the electrolyte composition. Generally, carbanogel particles tend to decompose and at least a portion of the CNM content of the carbanogel is converted to carbon monoxide (CO) at temperatures above 900°C. However, some CNM structures can be maintained in the carbanogel at temperatures of about 1000°C in the presence of high CO2 gas pressure. For example, pure Li2CO3, Na2CO3 or K2CO3 electrolytes have melting points of about 723°C, 851°C and 891°C, respectively, while mixtures of Li2CO3 and Na2CO3 can melt at temperatures below about 700°C, and Li x Na y K z The CO3 eutectic melts at 399° C. Thus, the heating step 107 can occur in the presence of high pressure CO2 in a narrower range of about 0° C. to about 1000° C., or about 15° C. to about 900° C., or about 399° C. to about 850° C.

[0048]

[0054] When the CB product is stripped of most, substantially all or all of its electrolyte content, the CB product loses the protection provided by the electrolyte. Thus, care may be required to prevent oxidative loss of the CNM product, such as, but not limited to, isolating the CB product from an oxygen-containing atmosphere 112 or the optional step of adding an oxygen-free protective gas, such as an inert gas that does not oxidize or react with the CB product. Non-limiting examples of such inert gases include nitrogen, argon, or a mixture of gases with a full complement of valence electrons.

[0049]

[0055] Without being limited by any particular theory, method step 100 and method 100A may combine fused residual electrolyte or bulk electrolyte (depending on whether and to what extent reducing step 105 is performed) with van der Waals between CNM structures to provide a driving force for assembling the carbanogel particles into continuous sheets of CB.

[0050]

[0056] As mentioned above, the CB product may define voids that may be left open. Alternatively, these voids may be partially, substantially completely, or completely filled with materials based on the application, such as strengthening agents, catalysts, dopants, magnetic materials, pharmaceuticals, or EMF shielding enhancing agents. Similarly, during the generating step 101 using an electrolysis process to create the CNM product, the CNM itself may be modified with strengthening agents, catalysts, dopants, magnetic materials, pharmaceuticals, or EMF shielding enhancing agents.

[0051]

[0057] Reinforcing agents that may be included in the void space of the CB product may include, but are not limited to, epoxy resins, resins and other polymers, cementitious materials, metals and alloys. Catalysts that may be included in the void space may include, but are not limited to, materials for promoting chemical or electrochemical reactions. Dopants that may be included in the void space may include, but are not limited to, boron, nitrogen, sulfur, phosphorus, and cobalt, aluminum, silicon, copper, silver, zinc, cerium, platinum, gold, ruthenium, osmium, tellurium, their respective oxides, salts, combinations thereof, and other materials that are incorporated into the structure of the CNM and that substantially affect the physical and chemical properties of the CNM and the carbanogel buckypaper made therefrom when incorporated in small relative amounts. When incorporated, dopants may enhance properties including, but are not limited to, conductivity, catalytic activity, and battery capacity. Magnetic materials that may be included in the void space of the CB product include, but are not limited to, one or more of iron, nickel, cobalt, gadolinium, samarium, neodymium, steel or carbides thereof and other alloys including one or more magnetic materials with ferromagnetic, paramagnetic, diamagnetic properties, and any combination thereof. The magnetic properties of the improved CB product include applications for flexible magnets, magnetic storage, and magnetic shielding.

[0052]

[0058] Known processes for producing buckypaper products require a dispersion step, e.g., ultrasonication, to provide uniform distribution of the CNM components in the buckypaper product. In contrast, according to embodiments of the present disclosure, and without being limited by any particular theory, the CNM and / or CB products in the carbanogel may already be uniformly distributed. Thus, embodiments of the present disclosure do not require such a CNM dispersion step, although this step may be added for blending to other additives or quality control. In embodiments of the present disclosure, a step of applying force to align the CNMs rather than dispersing them is additionally used in embodiments of the present disclosure. Additionally, liquid may be added prior to the applying step 108 to maintain a more uniform layering of the carbanogel particles. These steps of alignment 113 may impart oriented, anisotropic properties to the CB product, and the alignment 113 step also provides improved properties to the CB product. For example, the imparted directional anisotropic properties may provide, without limitation, improved strength, conductivity, and directional interaction with visible and other electromagnetic radiation compared to other buckypaper and CB products of the present disclosure that do not undergo the alignment step 113. The alignment 113 step may include applying one or more alignment forces, such as linear, radial, cylindrical, spherical, or other geometric forces, to produce anisotropic linear, radial, cylindrical, spherical, or other directional geometric shapes in the carbanogel.

[0053]

[0059] The alignment 113 step may be mechanically, electrically, magnetically, or any combination thereof applied to the CNM components in the carbanogel and / or CB product during method 100, 100A. The alignment 113 step by mechanical alignment may be accomplished by applying shear forces, for example, by pulling or rotating during one or more of the processing steps, or by pulling a piston to apply forming pressure to the CNMs in the carbanogel and / or CB product. Alternatively, the shear forces may be applied directionally to increase CNM entanglement rather than CNM alignment.

[0054]

[0060] The step of alignment 113 by electrical alignment may be achieved by applying an orienting electric field to the CNMs in the carbanogel and / or in the CB product during the method 100, 100A. The step of alignment 113 by magnetic alignment may be achieved by applying an orienting magnetic field during the method 100, 100A. The operating parameters of the generating step 101 may be selected such that the electrolysis process creates magnetic CNMs. For example, the operating parameters may be selected to add metal or metal carbide during the electrolysis process. Without being limited by any particular theory, the reduction in distance of the magnetic field rather than the electric field during magnetic alignment may be offset more than during electrical alignment due to competing random disorder of Brownian motion, which increases with increasing temperature and freedom of motion and decreases with increasing molecular weight and viscosity. Thus, the step of alignment 113 may be improved by decreasing the temperature and increasing the viscosity of the carbanogel.

[0055]

[0061] FIG. 5 is a first example of a CB made from CO2. The example is generally black and the figure has been lightened to enhance the contrast. The first CB example was made using electrolysis to convert CO2 to a carbanogel. The carbanogel was made in an apparatus 10 using a steel stainless steel case 304 in a Li2CO3 molten electrolyte at 750°C with a Muntz brass cathode and a stainless steel 304 anode producing a CNT carbanogel product. Carbogels were also made from the CO2CNT product when the cathode was changed to Monel or Ni alloys, such as Inconel, Nichrome and Ni-iron and Ni-copper alloys, and the anode was changed to Inconel, Nichrome and Ni-iron and Ni-copper alloys. 0.2 grams of this carbanogel product was cleaned with hydrochloric acid (HCl), mixed in 300 mL of isopropyl alcohol, and then ultrasonically decomposed for 30 minutes for uniform dispersion. The mixture was then poured into a vacuum filter assembly (nylon membrane filter, 0.2 μm pores, 47 mm diameter) and the liquid was drawn off under vacuum; a wide range of filter pore sizes and solvents have been found to be effective for forming buckypaper from CO2 converted to carbanogel by this method. The CNTs had mixed orientations in the forming CB or were aligned when mechanical, electric or magnetic forces were applied during the liquid (alcohol) removal stage. Once all discernible alcohol had passed through the filter, the filter was removed and dried overnight at room temperature. The resulting CB was removed from the nylon membrane filter and had a thickness of 180 μm.

[0056]

[0062] FIG. 6 is a second example of a CB made from CO2. The example is generally black and the figure has been lightened to enhance contrast. The CB example in FIG. 6 was made from CO2 converted to a carbanogel as described in the preceding example, but instead of chemical washing, the electrolyte content of the carbanogel was reduced by compression. Specifically, the carbanogel was generated at the cathode and then compressed through a mesh or layer of mesh at high temperature while still containing both solid CNM and molten electrolyte. To produce the CB in FIG. 6, a pressure of 500 psi at 750° C. was used. When pressures of 1000 psi or more were applied, similar but thinner CBs were produced, while pressures of less than 500 psi produced thicker CBs. The CB shown in FIG. 6 has a diameter of about 350 mm, and one about twice as large was also made applying a pressure of 500 psi. The carbanogel has also been pressed directly onto the hot cathode (after removal from the case) or pressed after transfer from the cathode as in this example. The carbanogel can be transferred while hot or after processing after transfer from the cathode (e.g., cooling, stripping, crushing and reheating to remelt the electrolyte in the carbanogel) as in this example. The screen mesh size used for pressing, measured in lines per inch, varies from 2 to 100 mesh size or from 100 to 1,000 mesh size or mesh size above 1,00 lines per inch to reduce electrolyte from the product. A mesh size of about 60 with a pore size of about 250 μm is particularly effective in addition to various larger sizes. Note that the pore size of 250 μm is much larger than the dimensions of the nanomaterials of the CNM in the CB. Without being bound by any theory, it is believed that CO2-converting buckypaper forms during compression because the larger size of the intermingled CNMs in the carbanogel are retained by the mesh while the electrolyte passes through the mesh. The resulting CB has a thickness that is linearly proportional to the initial mass of the carbanogel and approximately inversely proportional to the applied pressure.

[0057]

[0063] FIG. 7 is an example of a carbanogel with reduced electrolyte by washing, as measured by scanning electron microscopy, SEM, shown at two different magnifications, 720x and 8600x. This example is of the CNT carbanogel prepared by CO2 electrolysis in the preceding example. The large particle size of the intermingled CNMs containing the carbanogel is evident in the first half of FIG. 7. This is the large 0.2 mm pore size in the first example or the mesh size of 250 μm in the second example. This allows the carbanogel to be easily formed from the fine suppression filter, despite the nano-scale dimensions of the carbanogel material in the lower part of FIG. 7. Following electrolysis, the carbanogel was peeled off from the cooled cathode and crushed. The crushed pieces of the carbanogel following washing with concentrated HCl are shown in the SEM image of FIG. 7, where the high purity of the CNTs and their orientation in various directions is evident. An alternative wash with dilute HCl acid similarly washed away electrolytes and metal impurities as measured by electron dispersive spectroscopy, EDS and thermogravimetric analysis, TGA. An alternative wash with either water or formic acid only removed primarily excess electrolytes and did not remove metal impurities. An alternative wash with either water, formic acid, or ammonium sulfate primarily removed excess electrolytes and did not remove metal impurities. Another alternative wash with combined hydrochloric acid and hydrogen peroxide, in this case ultrasonic disintegration rather than mixing of the carbanogel in a solution of concentrated HCl and 35% H2O2, removed excess electrolytes, metal impurities, and even amorphous carbon impurities. Similarly, other chemical oxidants, such as hydrochloric acid and potassium permagnate, were observed to be effective at sufficient dilution, and electrochemically generated oxidants were generated. Amorphous carbon is more susceptible to oxidation than the more robust stacked graphene CNT structures, as measured by its lower combustion temperature in TGA compared to carbon nanotubes, and can be removed as an impurity by chemical, electrochemical, or thermal oxidation.As a further example of reducing the impurity content of the carbanogel, the carbanogel was heated to 300° C. following an HCl wash, as measured by mass loss, by TGA, as measured by SEM, to largely remove the amorphous carbon impurities and retain the CNTs containing carbanogel.

[0058]

[0064] CB products made according to embodiments of the present disclosure may be used in a variety of applications, including, but not limited to, linings, flame retardants, or shields. However, the CB products of the present disclosure may also be used as components of composites, such as, but not limited to, laminates that include at least one layer of the CB product with other non-CB materials, imparting enhanced properties to those other non-CB materials. For example, buckypaper and composites made with buckypaper exhibit shape memory properties under thermal, mechanical, electrical, magnetic, optical, or chemically active conditions, which may be imparted to laminate products that include one or more layers of the CB product and one or more layers of non-CB materials. This shape memory effect is facilitated by including anisotropic properties in the CB product, as described above. Additionally, the electrical and thermal conductivity of the CB product may provide superior properties when used in heating element or radiator applications.

[0059]

[0065] Other applications of CB buckypaper products that specifically take advantage of the superior CNM properties of carbanogel include, but are not limited to, (a) light-weight tooling applications for fast, safe and rapid changeover; (b) harder tools for better drilling, impact and / or sawing; (c) tools for better thermal management; (d) super strong and foldable materials; (e) as precursors to fibers and fabrics; (e) as high density storage packets for transport and delivery of CNMs and for general sequestration of CO2; (f) super light, super absorbent sponges; (g) as laminate sheets for composites; (h) for ballistic or EMF shielding; (j) for making composites with large amounts of CNMs by infiltrating pores in the structure; (k) parachutes and drag enhancers; (l) for studying the bulk properties of carbon nanomaterials.

[0060]

[0066] Other uses of CB products made according to embodiments of the present disclosure include products that combine the benefits of two or more superior CNM properties, such as, but not limited to, structural materials that provide dual uses for additionally reducing weight, material cost / materials used, and / or increasing capacity, such as (i) structural and electrical energy storage, or (ii) structural and thermal energy storage, (iii) structural and as electrical conduits or wires, (iv) structural and as strain or safety sensors to gather real-time data on material performance, (v) structural and acting as catalysts, (vi) structural and as thermal conduits, etc. There are also applications and uses of CB products made according to embodiments of the present disclosure for increasing safety, for example, by being used in heat dissipation members to dissipate high heat in applications where fire is a concern.

Claims

1. 1. A method for preparing a carbanogel bucky paper (CB) product, comprising: a. Carbon dioxide (CO) in the molten electrolyte 2 receiving a carbanogel produced by an electrolysis process to partition a carbon nanomaterial (CNM) and the molten electrolyte, the carbanogel either cooled or uncooled, b. placing the carbanogel into a mold; c. compressing the carbanogel to form the CB product. The method includes:

2. 2. The method of claim 1, wherein the placing step follows the step of receiving the carbanogel at a temperature above a melting point of an electrolyte contained in the molten electrolyte.

3. 2. The method of claim 1, wherein the placing step follows the step of receiving the carbanogel at a temperature below a melting point of an electrolyte contained in the molten electrolyte.

4. The method of claim 1 , wherein the step of placing follows a step of treating the carbanogel.

5. The method of claim 4, wherein the processing step includes one or more of cooling the carbanogel, extracting the carbanogel either cooled or uncooled, and crushing the carbanogel either cooled or uncooled.

6. The method of claim 1 , wherein the compressing step is repeated.

7. The method of claim 1 , wherein the compressing step includes applying a pressure of between 1 pound per square inch (psi) and 2,000 psi.

8. The method of claim 1 , wherein the compressing step comprises applying a pressure greater than about 2000 psi.

9. The method of claim 1 further comprising the step of reducing the amount of the molten electrolyte in the carbanogel.

10. 10. The method of claim 9, wherein the reducing step comprises pressing, reacting, washing, filtering, and any combination thereof.

11. 10. The method of claim 1, wherein the CNMs comprise spherical nanocarbons, solid nano-onions, hollow nano-onions, cylindrical allotropic nanocarbons, planar allotropic nanocarbons, helical allotropic nanocarbons, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface modified or metal coated CNMs, amorphous nanocarbons without graphitic features, amorphous nanocarbons without graphitic properties, and any combination thereof.

12. The method of claim 1, further comprising the step of applying heat before, during or after the step of applying pressure, the heat being between 0°C and 1000°C.

13. The method of claim 12 , further comprising aligning the CNMs by applying an alignment force before, during or after the applying pressure step.

14. The method of claim 13 , wherein the aligning force is a mechanical force, an electric current, a magnetic field, and any combination thereof.

15. 14. The method of claim 13, wherein the aligning force is of a radial, cylindrical, spherical or other shape to produce a linear, radial, cylindrical, spherical or other directional shape to impart one or more anisotropic properties to the CB product.

16. 10. The method of claim 1, further comprising the step of applying a void-filling agent to partially or substantially completely fill voids in the carbanogel, the CB product, or both.

17. 17. The method of claim 16, wherein the void-filling agent is a reinforcing agent, a catalyst, a dopant, a magnetic material, a drug, an electromagnetic force shielding agent, or a combination thereof.

18. 20. The method of claim 17, wherein the toughening agent comprises an epoxy, a resin, another polymer, a cementitious material, a metal, an alloy, and any combination thereof.

19. 20. The method of claim 17, wherein the catalyst comprises an epoxy, a resin, another polymer, a cementitious material, a metal, an alloy, and any combination thereof.

20. 18. The method of claim 17, wherein the dopants include boron, nitrogen, sulfur, phosphorus, cobalt, aluminum, silicon, cerium, platinum, gold, ruthenium, osmium, tellurium, tungsten, oxides of each, salts of each, and any combination thereof.

21. 20. The method of claim 17, wherein the magnetic material is iron, nickel, cobalt, gadolinium, samarium, neodymium, steel, carbides of each, other alloys including one or more magnetic materials with ferromagnetic, paramagnetic, diamagnetic properties, and any combination thereof.

22. The method of claim 1, further comprising the step of applying heat before, during or after the step of applying pressure, the heat being between 15°C and 900°C.

23. The method of claim 1, further comprising the step of applying heat before, during or after the step of applying pressure, the heat being between 399°C and 850°C.